Factors associated with medical students speaking-up about medical errors: A cross-sectional study. (2nd January 2022) - Chen, Yi-Chun; Issenberg, S. Barry; Issenberg, Zachary; Chen, Hui-Wen; Kang, Yi-No; Wu, Jen-Chieh
Abstract: Background: Training medical students to speak up when they witness a potential error is an important competency for patient safety, but details regarding the barriers that prevent medical students from effectively communicating are lacking. Therefore, this study aimed at exploring the factors affecting medical students' willingness to speak up for patient safety when a medical error was observed. Methods: This is a cross-sectional study at a medical university in Taiwan, and 151 medical students in clinical clerkship completed a survey including demographic characteristics, conflict of interests/social relationship, personal capability, and personality and characteristics of senior staff domains. Data were analyzed using t -test. Results: Three of five items in the conflict of interests/social relationship domain showed statistically significant importance, including 'I am afraid of being punished' (Mean difference, MD = 0.37; p  < 0.01), 'I do not want to break unspoken rules' (MD = 0.55; p  < 0.01), and 'I do not want to have bad team relationship' (MD = 0.58; p  < 0.01). Two items (perception of knowledge/understanding and communication skills) in the personal capability domain were significantly important to speaking up. Six of 10 items in personality and characteristics of senior staff domain were rated significantly important in deciding to speak up. The top three factors of them were senior personnel with 'Grumpy' personality (MD = 1.20; p  < 0.01), 'hierarchy gap' (MD = 1.12; p  < 0.01), and senior personnel with 'Stubborn' personality (MD = 1.06; p  < 0.01). Conclusion: Our findings demonstrated medical students' perspectives on barriers to speaking up in the event of medical error. Some factors related to characteristics of senior staff could compromise medical students' ability to speak up in the event of medical error. These results might be important for medical educators in designing personalized educational activities related to medical students' ability to speak up for patient safety.